2017
DOI: 10.5125/jkaoms.2017.43.4.247
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of quality of life of families with children born with cleft lip and/or palate before and after surgical treatment

Abstract: ObjectivesThe aim of this study was to compare the quality of life (QoL) of parents/caregivers of children with cleft lip and/or palate before and after surgical repair of an orofacial cleft.Materials and MethodsFamilies of subjects who required either primary or secondary orofacial cleft repair who satisfied the inclusion criteria were recruited. A preoperative and postoperative health-related QoL questionnaire, the ‘Impact on Family Scale’ (IOFS), was applied in order to detect the subjectively perceived QoL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
27
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 35 publications
4
27
1
1
Order By: Relevance
“…The role of oral health and oral function in OHRQoL is well established. [17][18][19] The fact that our study found no significant differences between the cleft and control groups in these domains is in keeping with the findings of other studies. This is attributed to the fact that while cleft lip and palate does cause dental anomalies such as missing or malformed teeth, they do not appear to affect oral health or oral function.…”
Section: Discussionsupporting
confidence: 93%
“…The role of oral health and oral function in OHRQoL is well established. [17][18][19] The fact that our study found no significant differences between the cleft and control groups in these domains is in keeping with the findings of other studies. This is attributed to the fact that while cleft lip and palate does cause dental anomalies such as missing or malformed teeth, they do not appear to affect oral health or oral function.…”
Section: Discussionsupporting
confidence: 93%
“…The different periods in cleft care, such as before or after surgery and settings of care such as home or hospital admission, may present different challenges to the caregivers and as previously hypothesized; care burden may differ along the care trajectory ( 19 ), and this was reflected in the study of Emeka et al that reported significant difference in the quality of life of family caregivers before and after cleft repair ( 20 ). The present study was carried out among family caregivers of cleft patients in the perioperative period, and this period may be associated with peculiar subjective and objective demands.…”
Section: Discussionmentioning
confidence: 97%
“…The most pronounced impacts, which most affected quality of life, were in the financial and social domains. Caregivers of children with cleft lip and palate need support from society, health professionals, friends and relatives (12) .…”
Section: Discussionmentioning
confidence: 99%
“…Considering that caring for a child with cleft lip and palate can lead to a worse perception of quality of life (12) , and that the burden can negatively influence this perception, it is essential to assess the correlation between these variables. A situational analysis allows planning and implementing actions to minimize the burden, favoring the health and well-being of caregivers.…”
Section: Introductionmentioning
confidence: 99%